Metabolic syndrome and non‐alcoholic fatty liver disease after liver or kidney transplantation. Issue 9 (4th February 2016) - Mikolasevic, Ivana; Orlic, Lidija; Hrstic, Irena; Milic, Sandra
Abstract : Transplantation is a definitive treatment option for patients with end‐stage liver disease, and for some patients with acute liver failure, hepatocellular carcinoma or end‐stage renal disease. Long‐term post‐transplantation complications have become an important medical issue, and cardiovascular diseases (CVD) are now the leading cause of mortality in liver or kidney transplant recipients. The increased prevalence of metabolic syndrome (MS) likely plays a role in the high incidence of post‐transplantation CVD. MS and its hepatic manifestation, non‐alcoholic fatty liver disease (NAFLD), are prevalent among the general population and in pre‐ and post‐transplantation settings. MS components are associated with recurrent or de novo NAFLD in transplant recipients, potentially influencing post‐transplantation survival. Moreover, recent data reveal an important association between NAFLD and risk of incident of chronic kidney disease (CKD). Therefore, NAFLD identification could represent an additional clinical feature for improving the stratification of liver and kidney transplant recipients with regards to risks of CVD, CKD and renal allograft dysfunction. All MS components are potentially modifiable; therefore, it is crucial that hepatologists, nephrologists and primary care physicians become more engaged in managing post‐transplantation metabolic complications. The present review discusses the recent clinical evidence regarding the importance of MS and its components after liver and kidney transplantation, as well as the link between MS and NAFLD after liver and kidney transplantation.